Butorphanol decreased the median effective concentration of ropivacaine in ultrasound-guided interscalene brachial plexus block - Hang Su; Juan Li; Jiping Zhang; Yiran Zhang; Faping Tu (PLoS ONE, 2026)
Background Combining butorphanol with local anesthesia can enhance the analgesic effect of local anesthesia and prolong the duration of action for nerve block anesthesia. In this study, we aimed to determine the effects of butorphanol on the median effective concentration (EC50) of ropivacaine in ultrasound-guided interscalene brachial plexus block (ISB). Methods This is a randomized, double-blind, up-and-down sequential allocation study. Fifty patients undergoing arthroscopic shoulder surgery under general anesthesia were randomly assigned to the ropivacaine group or the butorphanol group in a 1:1 ratio. The former received 20 mL of ropivacaine for ultrasound-guided ISB, and the latter received a mixture containing 1 mg butorphanol and 20 mL ropivacaine. The concentration of ropivacaine for the first patient was 0.4%, and the ropivacaine concentration for the next patient was determined on the basis of the response of the previous patient to 0.4% ropivacaine using Dixon’s up-and-down sequential method with a ratio of 1:1.1. Results Forty patients completed this study. The bootstrap EC50 of ropivacaine was significantly lower in the butorphanol group (0.24%, 95% CI: 0.23%–0.24%) than in the ropivacaine group (0.30%, 95% CI: 0.29%–0.31%). Compared with the ropivacaine group, the dosage of ropivacaine in the butorphanol group decreased significantly during the test. Postoperative visual analog scale scores at 8 h and 12 h were lower in the butorphanol group than in the ropivacaine group, and the need for salvage analgesia within 24 h after surgery was significantly lower in the butorphanol group. Conclusion Butorphanol decreased the EC50 of ropivacaine required for ISB in patients undergoing arthroscopic shoulder surgery. Trial registration It was registered on October 30th, 2022 (available at http://www.chictr.org.cn , identifier: ChiCTR2200065164).